Infection control measures among dental practitioners in a Southern state of India: A cross-sectional study - Vikram Simha Bommireddy; Srinivas Pachava; Suresh Sanikommu; Narayana Rao Vinnakota; Devaki Talluri; Bhanu Kiran Ghanta (Wolters Kluwer Medknow Publications, 2016)
Introduction: The identification of hepatitis B virus, human immunodeficiency virus as an occupational hazard in dentistry urged all practicing dentists, dental auxiliaries, and dental laboratories to employ appropriate infection control procedures. Aim: The aim of this study to investigate whether there is a scope for improvement in the practice of infection control measures. Materials and Methods: A cross-sectional study was conducted using self-administered questionnaire, to obtain information about procedures used for prevention of cross-infection in dental practices. The study subjects, dental practitioners in Guntur district, were obtained using snowball technique. Data were analyzed using SPSS version 19 software. Descriptive and inferential statistics were used to summarize the results and P < 0.05 was considered statistically significant. Results: The mean age of the study population was 36.48 ± 8.94 years. Of the 183 study subjects, 136 (74.3%) were males and 47 (25.7%) females. Of the total practitioners, 45% usually treated ≥10 patients per day, and 52% had the habit of taking medical history for all patients. Statistically significant difference had been found between the practitioners with Bachelor of Dental Surgery and Master of Dental Surgery as their highest qualification, regarding the method of sterilization of handpiece (P = 0.03). Conclusion: This study result suggests that there was a scope for improvement in the practice of infection control procedures among dental care professionals.